Research article on Correlations of CBR-A Literature - Vishal Yadav, Nasir Ali Lone,Rajesh Goyal, (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2017)
This paper summarizes the ongoing researches about the California bearing ratio which is most use in direct method to assess the stiffness modulus and shear strength of sub grade in the design of flexible pavement. Many studies regarding CBR values of different types of soil , that have been carried out earlier were studied, it has been found that CBR value varies with different properties possessed by the soil.CBR value of soil depends on many factors like maximum dry density (MDD),optimum moisture content(OMC),liquid limit(LL), unconfined compressive strength, percent fines etc. Determination of CBR is a bit lengthy and time consuming process so a correlation can be developed between the CBR values and Index properties of soil, so that the sub grade strength can be determined.